Challenges for the conservation of marine small natural features. (July 2017) - Lundquist, Carolyn J.; Bulmer, Richard H.; Clark, Malcolm R.; Hillman, Jenny R.; Nelson, Wendy A.; Norrie, Craig R.; Rowden, Ashley A.; Tracey, Dianne M.; Hewitt, Judi E.
Abstract: Seascapes contain a mosaic of ecosystem types, including 'small natural features' that support a diverse fauna and flora, and provide ecosystem services disproportionate to their size. These include tropical coral reefs, seagrass meadows, rhodolith beds, kelp and mangrove forests as well as deep-sea coral reefs, sponge gardens and hydrothermal vents. The contributions of coral reefs, mangrove forests and seagrass meadows are well recognised as important components of tropical marine seascapes. In temperate regions, hotspots of primary productivity such as kelp forests, and vegetation-based ecosystems found at coastal margins play significant roles in nutrient and sediment trapping and coastal protection. Biogenic features in coastal regions can also play important roles, including shellfish reefs, sponge gardens and macroalgal mats that provide physical structure within soft sediment ecosystems. Similar biogenic features are found in the deep sea, which often occur associated with seamounts, canyon features, cold seeps and hydrothermal vents. Many marine small natural features are globally threatened as they are found at the interface with human-influenced landscapes (coastal ecosystems) or are the focus of resource exploitation (e.g., trawling for fish associated with seamounts and canyons). Challenges in management are, however, consistent across depths, and highlight the restricted spatial extent of such features, and the limited information typically available on their distributions, and the ecosystem services they provide. Numerous strategies can be utilized to sustainably manage, protect, create and restore these marine small natural features and their associated biodiversity. Highlights: Small natural features are prevalent in marine seascapes. Marine SNFs contribute disproportionately to a range of ecosystem services. Marine SNFs are impacted by a range of threats. Sustainable management strategies are required for their conservation.